Unveiling hepatitis B biomarkers through genomic network analysis - Wirawan Adikusuma; Firdayani Firdayani; Lalu Muhammad Irham; Ichtiarini Nurullita Santri; Yohane Vincent Abero Phiri; Dian Ayu Eka Pitaloka; Rockie Chong; Made Ary Sarasmita; Rahmat Dani Satria (Egyptian Journal of Medical Human Genetics)
Abstract Background The infection caused by the Hepatitis B virus (HBV) poses a significant challenge to global health. However, identifying and prioritizing functional biomarkers associated with the disease will allow more focused efforts for pre-clinical investigation. This study aimed to employ advanced genomic networks and bioinformatics tools to prioritize biomarkers for HBV. Results Comprehensive curation from six well-known databases yields a set of 495 HBV-associated genes based on gene ontology enrichment, pathway enrichment and protein–protein interaction analyses. Further functional gene network analyses identified 10 hub genes (IL-6, TNF, STAT3, CD4, IL-10, STAT1, IL-1B, AKT1, IL-2, and TLR4), warranting further investigation. Among these genes, IL-6, TNF, and STAT3 emerged as promising biomarkers for HBV through CytoHubba analysis. Conclusions Overall, this study offers a genomic network-centric approach to identify and prioritize potential HBV biomarkers to provide valuable insights into its pathogenesis.